Palladium catalysed allene carbocyclisation - Li, M (2010)
In this thesis, firstly, a Pd-catalysed diastereoselective carbocyclisation of allenes with aryl halides or vinyl iodides was designed and developed to form arylative or vinylative spirolactam compounds. High yields and diastereoselectivities were obtained in the presence of Pd2(dba)3/dppe and K2CO3 in DMSO at 70 °C, particularly when spiropiperidin-2-ones were formed. The method is simple to perform and broad in scope. Having established the diastereoselective methodology for the arylative or vinylative allene carbocyclisation, a Pd-catalysed enantioselective version was developed by using bisoxazolines as chiral ligands. Aryl halides and vinyl iodides were investigated in this carbocyclisation. High yields and enantioselectivities were obtained in the presence of Pd(OAc)2, a bisoxazoline ligand L7d derived from L-isoleucine and Ag3PO4 in 1,2-dichloroethane at 70 °C. No olefin isomerisation was observed when cis-vinyl iodides were used. The method is mild, efficient and broad in scope. A palladium catalysed diastereoselective allene carbocyclisation reaction was developed via enamine catalysis and palladium catalysis, which allows for the efficient carbocyclisation of formyl or ketone allenes. Good yields and high diastereoselectivities were obtained in the presence of Pd(OAc)2 and pyrrolidine in toluene at 60 °C when formyl allenes were investigated. The cyclisation is diastereoselective and can also performed as a catalytic asymmetric reaction by using prolinol derivatives as chiral catalysts. Good yields and high diastereo- and enantioselectivities were obtained in the presence of catalyst (S)-L19. Additionally, a boronic acid catalysed ene carbocyclisation of acetylenic dicarbonyl compounds was developed. An attempted transesterification of a β-ketoester substrate bearing a pendent terminal alkyne substituent at the β-position led to the discovery of an efficient 3-nitrobenzeneboronic acid catalysed ene carbocyclisation of acetylenic dicarbonyl compounds. The reaction is easy to perform, efficient, broad in scope and provides a convenient transition metal-free alternative to existing catalytic protocols.